Internal Limiting Membrane Flap in the Management of Retinal Detachment due to Paracentral Retinal Breaks - Yen-Chih Chen; Chung-May Yang; San-Ni Chen (Journal of Ophthalmology)
Purpose. To describe the technique and outcomes of using either inverted or free internal limiting membrane flap in the management of retinal detachment due to paracentral retinal breaks. Methods. This retrospective observational case series includes nine patients who received surgery for retinal detachment due to paracentral retinal breaks developed either from primary rhegmatogenous origin, or secondary iatrogenic retinal breaks after prior membrane peeling, or during surgery for tractional retinal detachment. Either inverted or free internal limiting membrane flaps were inserted in the identified breaks, followed by air fluid exchange and gas tamponade. Visual acuity and structural changes were evaluated. Results. Nine eyes were included. One had primary rhegmatogenous retinal detachment, one had highly myopic eye with peripapillary atrophic hole, three had secondary retinal detachment after membrane peeling for foveoschisis or macular pucker, one had recurrent retinal detachment due to proliferative vitreoretinopathy, one had combination of tractional and rhegmatogenous retinal detachment, and two had iatrogenic breaks during surgery. The retinal breaks of all eyes were sealed with retina attached postoperatively. Visual acuity in logarithm of minimal angle of resolution improved from 1.18 ± 0.55 preoperatively to 0.74 ± 0.47 postoperatively (p=0.04). Conclusion. Internal limiting membrane flap technique can be a surgical approach selectively for retinal detachment due to paracentral retinal breaks with difficulty for laser application. The retina can be attached successfully and achieve good visual outcome without major complication. This trial is registered with NCT03707015.